Struktur Kepribadian Tokoh dalam Kumpulan Cerpen Sagra yang Berjudul Api Sita Karya Oka Rusmini - Rakhmawati, Sabrina Andin (UM Purwokerto Press, 2024)
The research below describes the personality structure of the main character Sita in the Sagra short story collection entitled Api Sita by Oka Rusmini. In this research, the method used is descriptive qualitative, then the approach used is the literary psychology approach, personality theory from Sigmund Freud which includes the id, ego and superego. This research data consists of words and actions as well as quotes related to the personality structure of the main character Sita. In this research, the main instrument is the researcher himself. Then the results obtained from this research show that the personality structure of the main character Sita in the Sagra short story collection entitled Api Sita by Oka Rusmini is divided into 3 elements, namely, id, ego and superego.